2009
DOI: 10.1515/cclm.2009.063
|View full text |Cite
|
Sign up to set email alerts
|

Recent insights into the role of dipeptidyl aminopeptidase IV (DPIV) and aminopeptidase N (APN) families in immune functions

Abstract: Summarizing data obtained from the usage of different non-selective and selective inhibitors of DPIV, DP8/9, FAP, and DPII, this review provides evidence that in addition to DPIV, DP8/9 also regulate the immune response via modulation of cell cycle progression and cytokine production. The strongest and most consistent effects in vitro were, however, observed with non-selective inhibitors for the suppression of DNA synthesis and cytokine production. Similar effects were provoked by APN inhibitors, which were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 29 publications
3
39
0
1
Order By: Relevance
“…Considering that DPP IV/CD26 is a member of a large S9b family of structurally homologous serine proteases that possess a unique catalytic activity, and since two recent studies have demonstrated a broad tissue distribution of DPP IV-like enzyme activity in both wild type and CD26 -/-, a possible explanation of results obtained in our study could be that other DPP IV-like protease are involved in the activation of the inflammatory response in animal model of colitis (Ansorge et al, 2009;Yu et al, 2009). Furthermore, it was recently demonstrated by Yazbeck and its coworkers (Yazbeck et al, 2008) that inhibition of DPP-like activity ameliorates the severity of inflammation in experimental colitis in mice.…”
Section: Dpp Iv/cd26 and Dpp Iv/cd26-like Activity In Dss-colitissupporting
confidence: 62%
“…Considering that DPP IV/CD26 is a member of a large S9b family of structurally homologous serine proteases that possess a unique catalytic activity, and since two recent studies have demonstrated a broad tissue distribution of DPP IV-like enzyme activity in both wild type and CD26 -/-, a possible explanation of results obtained in our study could be that other DPP IV-like protease are involved in the activation of the inflammatory response in animal model of colitis (Ansorge et al, 2009;Yu et al, 2009). Furthermore, it was recently demonstrated by Yazbeck and its coworkers (Yazbeck et al, 2008) that inhibition of DPP-like activity ameliorates the severity of inflammation in experimental colitis in mice.…”
Section: Dpp Iv/cd26 and Dpp Iv/cd26-like Activity In Dss-colitissupporting
confidence: 62%
“…It was reported in 2009 that a new inhibitor for both CD26 and APN was developed for the treatment of inflammatory skin diseases and recruited to a clinical phase II study [8]. On the other hand, the effects of DPP-IV inhibitors on the immune system have not been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…CD26 is proposed to function as a keratinocyte activation antigen (Novelli et al, 1996). Moreover, CD26 inhibitors, currently used to manage type-2 diabetes, are being evaluated as treatments for psoriasis (Ansorge et al, 2009). CD26 is expressed in the differentiating epidermal layers and thus the upregulation in InvEE transgenic mice is correlated with the increased number of differentiated cell layers.…”
Section: Discussionmentioning
confidence: 99%